A New Translinear-Based Dual-Output Square-Rooting Circuit - Montree Kumngern; Kobchai Dejhan (My University, 2008)
A new wide input range square-rooting circuit is presented. The proposed circuit consists of a dual translinear loop, an absolute value circuit, and current mirrors. A current-mode technique is used to provide wide input range with simple circuitry. The output signal of the proposed circuit is the current which is proportional to the square root of input current. The proposed square-rooting circuit was confirmed by using PSpice simulator program. The simulation results demonstrate that the proposed circuit provides the excellent temperature stability with wide input current range.
Keywords: Square root; Square (algebra); SIGNAL (programming language); RL circuit; Root mean square; Sensor Technology and Measurement Systems